Molecular detection of gene encodes a β-tubulin protein in Haemonchus contortus in sheep in Al-Qadisiyah province, Iraq - Athraa N. Abed; Monyer A. Al-Fatlawi (Iraqi Journal of Veterinary Sciences, 2024)
β-tubulin protein is essential to parasitic resistance against widely used anthelmintic drugs. Many world countries are facing major challenges due to the failure of anthelmintic drugs, due to resistance, to eliminate parasitic infection in different animals, mainly sheep. So, there is a significant need to increase research focusing on parasites' resistance components, especially β-tubulin. Accordingly, the present study was conducted to identify and examine the genetic evolution of the β-tubulin gene responsible for synthesizing the β-tubulin protein in Haemonchus contortus in sheep. Here, 250 slaughtered sheep were explored, and 21 nematodes were collected and utilized in microscopic (10 nematodes) by placing each worm on a glass slide and exploring it under a light microscope at 10X magnification. In addition, 11 nematodes were set for molecular (PCR and sequencing) methods. The microscopic detection demonstrated the identification of the worm. The results revealed the amplification of the gene region in 11 worms. The sequencing of the nematodes showed the identification of 10 isolates closely similar to isolates from Sweden, with a similarity rate of up to 98%. The study's data report the major presence of the β-tubulin gene, which might be responsible for the drug due to drug resistance, and reveal important information about the genetic evolution of this gene that presents critical data about drug resistance development in the current study isolates of Haemonchus contortus.